Altmetrics: Present and future – panel. Issue 1 (2013) - ,; Bar‐Ilan, Judit; Sugimoto, Cassidy; Gunn, Willian; Haustein, Stefanie; Konkiel, Stacy; Larivière, Vincent; Lin, Jennifer
Abstract: Scholars are increasingly incorporating social media tools like blogs, Twitter, and Mendeley into their professional communication. Altmetrics tracks usage of these and similar tools to measure scholarly influence on the social Web. Altmetrics researchers and practitioners have amassed a growing body of literature and working tools to gather and analyze altmetrics and there is growing interest in this emerging subfield of scientometrics. In this panel, sponsored by SIG/MET, we will present results demonstrating the utility of alternative metrics from a variety of stakeholders: researchers, librarians, publishers and those participating in academic social media sites. We will discuss and debate the value and validity of such metrics with strong degrees of participation from the audience encouraged. Metrics, for better or worse, have had a presence in the lives of scholars–we will discuss the challenges and opportunities of altmetrics for the future.